Otimização da purificação e caracterização adicional de uma desintegrina-RGD recombinante de Bothrops alternatus e seu efeito em células endoteliais humanas (HUVEC) - Pontes, Carmen Lucia Salla (Universidade Federal de São Carlos, 2006)
Disintegrins are snake venom protein, of low molecular weight, rich in cysteines and RGDcontaining peptides that bind specifically to integrins αIIbβ3, α5β1, and αvβ3 expressed on platelets, endothelial and tumor cells. The biological effects of these peptides are related with biological process of cellular adhesion where receptors called integrins are presents. This dissertation describes the optimization of purification and additional characterization of a recombinant RGD-disintegrin of Bothrops alternatus, DisBa-01.. The DisBa-01 is a recombinant RGD-disintegrin, which interacts with αIIbβ3 integrin, inhibiting platelet aggregation and proliferation of endothelial and some tumor cells. In this work, a new protocol of purification was proposed for most efficient purification of the DisBa-01. The recombinant disintegrin, DisBa-01, was expressed in an optimizedbacterial system (Escherichia coli BL21(DE3) pET28a+DisBa-01) and purified by affinity chromatography. In this new protocol, the product of the purification in nickel column is submitted ion exchange chromatography. The use of the ion exchange chromatography as second step for purification increased the purity degree and the protein yield. The purified protein had its N-Terminal portion sequenced in 20 amino acids residues and its molecular mass determined by mass spectrometry. The mass spectrometry assay confirmed the mass of the DisBa-01 as 11.658 Da. The RGD-disintegrin pure had the tag of polihistidinas removed with thrombin. The cleavage of the tag of histidinas with thrombin was efficient. Polyclonal antibodies against DisBa-01 have also been produced in mice. The reactivity of these antibodies was observed through imunoblotting. These results provided one better form of obtain the pure protein as well as significant additional information for a better characterization of recombinant RGDdisintegrin, DisBa-01, which could be useful for the study of RGD-disintegrin, recombinant or native, and integrin.
Keywords: Bioquímica; Desintegrina; Anticorpos policlonais; Proteínas recombinantes; RGD-disintegrin recombinant; Bothrops alternatus; N-terminal sequence; Mass spectrometry; Purification; CIENCIAS BIOLOGICAS::GENETICA